Financial Sector Assessment Update : Albania - World Bank (World Bank, Washington, DC, 2014)
Although the Albanian financial system withstood the shocks of 2008 global crisis relatively well, it continues to operate in highly uncertain macroeconomic environment, which triggers increased vulnerabilities in the system. The decline in profitability, growing non-performing loans (NPLs), substantial level of euroization, continued deleveraging of foreign bank subsidiaries and significant investments in government bonds in the absence of active secondary market are the main challenges that banking system faces. Given strong trade and financial links with euro area, the financial system and real sector in general are increasingly vulnerable to external shocks as well. Since 2007 the Bank of Albania (BoA) has introduced several macro-prudential measures to safeguard financial stability in the country. Higher risk weights and stricter loan-to-value and debt-to-income ratios were placed on banks surpassing twin limits on the rate of credit growth and NPL levels. A second set of macro-prudential policies was put in place in late 2011 to limit contagion risks and international spillovers: (i) foreign bank branches were converted into subsidiaries; (ii) liquidity regulations were tightened; and (iii) the regulation on related-party exposure was enhanced. In addition to that, the risk weights for unhedged borrowers were increased to 150 percent and a limit of such loans was set to 400 percent of capital. Overall, financial reporting legislation in Albania has improved recently and has a high degree of alignment with the acquis communautaire of the European Union (EU).